OPTIMASI BIAYA PONDASI BORED PILE DENGAN METODE METAHEURISTIK - Leonard Chandra; Doddy Prayogo; Y Teddy Susanto (Program Studi Magister Teknik Sipil - Petra Christian University, 2021)
Foundation is part of the building structure to transfer the load from upper structure to soil layer. A deep foundation is used when the hard soil layer is located far below the soil surface. To design an optimal and economical deep foundation that still meet the safety requirements, Ultimate Limit State (ULS), Serviceability Limit State (SLS), and economic are required. Previous studies indicate that metaheuristic method can be used as an alternative to solve existing optimization problems. Therefore, this study uses metaheuristic methods which are Particle Swarm Optimization (PSO) and Symbiotic Organism Search (SOS) to solve the optimization of deep foundation. In this study, optimization was carried out for case studies of four and nine story buildings which used bored pile foundation. The result showed that metaheuristic method was able to find the optimal deep foundation dimensions.